Persistence as transition: a new perspective on persistence - Aoyama, Shinya (2018)
What is persistence? This is the most general question in this dissertation. According to current standard theories of persistence (i.e. endurantism, perdurantism, and exdurantism), an object persists by 3-D objects being located or existing at more than one time. That is, they understand persistence in terms of location along a fourth dimension. In this dissertation, I offer a new alternative framework for persistence, which is based on the Flux-first view proposed by Stephen Barker. In this new idea, persistence is not connected with locations long the fourth dimension. Rather, it is understood in terms of irreducible transition along the fourth dimension. That is, a concrete object persists not by being located at more than one time but by irreducibly transiting along the fourth dimension.